C and N stocks are not impacted by land use change from Brazilian Savanna (Cerrado) to agriculture despite changes in soil fertility and microbial abundances - Lammel, D.R.; Butterbach-Bahl, Klaus; Cerri, C.E.P.; Louis, S.; Schnitzler, J.P.; Feigl, B.J.; Cerri, C.C. (Wiley, 2017)
Central Brazil is the region with the most dynamic agriculture expansion worldwide, where tropical forests and Cerrado (Brazilian savanna) are converted to pastures and crop fields. Following deforestation, agricultural practices, such as fertilization, tillage and crop rotations, alter soil parameters and affect microbial abundances and the C and N cycles. The objective of this study was to compare changes in soil fertility, stocks of soil C and N, microbial biomass, and abundance of bacteria, fungi and archaea in Cerrado soils following land use change to crops (soybean/corn/cotton) and pasture (the perennial forage grass Brachiaria brizantha A. Rich.). Agriculture increased soil fertility and conserved soil C and N since their absolute concentration values were highest in agriculture soils and the C and N stocks adjusted by soil density were similar to the native vegetation soils. At the same time, agriculture changed the microbial abundances (decrease of microbial biomass C and N, increase of archaea, and reduction of bacteria and fungi at the crop sites), and N dynamics (increase of soil ammonium and nitrate concentrations). Even if these changes can be beneficial for food and agricultural commodities production, all these soil alterations should be further investigated due to their possible unknown effects on biosphere–hydrosphere–atmosphere exchange processes such as greenhouse gases emissions and nitrate leaching.